Developmental Vitamin D Deficiency in the Rat Impairs Recognition Memory, but Has No Effect on Social Approach or Hedonia - Overeem, Kathie (Nutrients, 2019)
Developmental vitamin D (DVD) deficiency is a risk factor for schizophrenia. In rodents we show that DVD-deficiency alters brain development and produces behavioral phenotypes in the offspring of relevance to the positive symptoms of schizophrenia. The aims of this study are to examine behavioral phenotypes specific to the cognitive and negative symptoms of schizophrenia in this model, and to vary the duration of vitamin D deficiency during gestation and beyond birth. We hypothesize that a longer duration of DVD-deficiency would result in greater behavioral impairments. Female vitamin D-deficient Sprague Dawley dams were mated at 10 weeks of age. Dietary vitamin D was reintroduced to dams and/or pups at different developmental time-points: Conception, Birth, Post-natal day (PND) 6 and PND21. Adult male and female offspring were assessed on a battery of behavioral tests, including sucrose preference, open field, novel object recognition (NOR), social approach and social novelty. We find that all windows of DVD-deficiency impaired NOR a cognitive measure that requires intact recognition memory. Sucrose consumption, social approach and social memory negative symptom-like phenotypes were unaffected by any maternal dietary manipulation. In addition, contrary to our hypothesis, we find that rats in the Conception group, that is the shortest duration of vitamin D deficiency, demonstrate increased locomotor activity, and decreased interaction time with novel objects. These findings have implications for the increasing number of studies examining the preclinical consequences of maternal vitamin D deficiency, and continue to suggest that adequate levels of maternal vitamin D are required for normal brain development.